PSTPIP1-associated myeloid-related proteinaemia inflammatory (PAMI) syndrome; a case presenting as a perinatal event with early central nervous system involvement? - Bethany Gillies Whiteside; Hannah Titheradge; Eslam Al-Abadi (BMC, 2022)
Abstract Background We report a three-year-old girl with a potentially unique phenotype of perinatal onset and neurovascular features who was found to have PAMI syndrome. We also compare her case to those previously reported and review the differences between the PSTPIP1-associated inflammatory diseases (PAID) phenotypes and genotypes. Case presentation The patient was found to have a heterozygous pathogenic variant in PSTPIP1 (c.748G > A p.E250K). This variant was shown to be absent in both parents and therefore de novo in the patient. A literature review was carried out through multiple databases using the terms PSTPIP1, PAID, PAPA syndrome and PAMI syndrome. This information was collected and used to form comparisons between the current literature and our reported case. Conclusions Our case contributes to the literature on PAMI syndrome whilst providing an example of a potentially unique clinical phenotype, giving insight into the pre-symptomatic phase of the condition. We highlight the importance of considering PAMI syndrome in the differential for early onset unexplained inflammation. In addition, we explore the possibility that perinatal neurovascular events could be an early feature of PAMI syndrome.